2020
DOI: 10.1002/aqc.3363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freshwater limitation on distribution patterns and habitat use of the West Indian manatee, Trichechus manatus, in the northern Brazilian coast

Abstract: The West Indian manatee (Trichechus manatus) is a Vulnerable species threatened by habitat loss in the coast of north‐eastern Brazil. This study investigates how the distribution and habitat use of the West Indian manatee is influenced by resource availability in a scenario of freshwater limitation. Land‐based and boat surveys were conducted to record manatee sightings and habitat use, in a total of 206 hours of observation. Manatee abundance was significantly influenced by freshwater availability, with greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The distance to freshwater (low salinity) and the water depth may be important determinants of the presence of Antillean manatees in some areas (Olivera‐Gómez & Mellink, 2005; Landero et al, 2014). A recent study on the north‐east Brazilian coast showed there was a greater abundance of manatees in areas where there was freshwater available (Favero et al, 2020). Habitat use may also be influenced by bathymetry in a similar manner to the influence of topography on the behaviour of herbivores (Sheppard et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance to freshwater (low salinity) and the water depth may be important determinants of the presence of Antillean manatees in some areas (Olivera‐Gómez & Mellink, 2005; Landero et al, 2014). A recent study on the north‐east Brazilian coast showed there was a greater abundance of manatees in areas where there was freshwater available (Favero et al, 2020). Habitat use may also be influenced by bathymetry in a similar manner to the influence of topography on the behaviour of herbivores (Sheppard et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study indicated a projected reduction of greater than 80% from 2014 to 2083, classifying it as ‘Critically Endangered’ (Meirelles et al, 2022). The distribution of the Antillean manatee within a given area is primarily influenced by the presence of aquatic vegetation (Lefebvre et al, 2001; Deutsch et al, 2003; Reich & Worthy, 2006; Marsh et al, 2012), sources of freshwater (Castelblanco‐Martínez et al, 2013; Landero et al, 2014; Alvarez‐Alemán et al, 2017; Favero et al, 2020), warm water (Deutsch et al, 2003; Jiménez, 2005), tides (Paludo & Langguth, 2002; Silva et al, 2011), water depth (Olivera‐Gómez & Mellink, 2005; Alves et al, 2013) and salinity (Olivera‐Gómez & Mellink, 2005; Landero et al, 2014; Alvarez‐Alemán et al, 2017). Anthropogenic activities can also affect the species occurrence, often causing changes in behaviour and forcing individuals to seek protection in more sheltered areas (King & Heinen, 2004; Miksis‐Olds & Wagner, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…De Lima et al (2012) suggested that food may not be the main motivating factor because these movements always start at a fidelity site where conditions are favourable for the animals. In a study of native manatees in the state of Piauí, areas of use were more strongly correlated with sources of freshwater than any other resource, suggesting that the distribution of manatees is driven by the proximity of freshwater (Favero et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Along the Brazilian coast, manatee populations are patchily distributed from Amapá to Alagoas (Luna et al, 2008; de Lima et al, 2011) and there is evidence of released animals using the coasts of Sergipe and Bahia states (Deutsch et al, 2008). The distribution of manatees is influenced by physiological (nutrition and metabolism; St Aubin & Lounsbury, 1990) and environmental factors (water salinity, temperature and depth, and availability of food resources; Lefebvre et al, 2001), freshwater supply (Favero et al, 2020) and anthropogenic habitat modifications (Deutsch et al, 2008). Manatees prefer naturally sheltered areas such as coves, bays and estuaries and are sensitive to disturbance caused by the construction and operation of cities, ports, marinas, shipyards, salt works, shrimp farms and other anthropogenic structures and activities in these areas (Aquasis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The other manatee species may also suffer as a result of reduced access to or degradation of freshwater ecosystems, however. For example, T. m. latirostris achieves higher digestive efficiency in freshwater (Worthy & Worthy 2014), suggesting that a higher biomass of marine food would be necessary if freshwater food resources were to be lost, and freshwater limitation may induce this species to concentrate around remaining availability and away from food (Favero et al 2020). Furthermore, many T. m. latirostris populations currently use warm effluent from power plants as thermal refugia (Haase et al 2020), and foraging oc curs in these areas (Allen et al 2014).…”
Section: Outlook and Future Directionsmentioning
confidence: 99%